Prevalence and Correlates of Viral Load Suppression and Human Immunodeficiency Virus (HIV) Drug Resistance Among Children and Adolescents in South Rift Valley and Kisumu, Kenya . (29th January 2022) - Tsikhutsu, Isaac; Bii, Margaret; Dear, Nicole; Ganesan, Kavitha; Kasembeli, Alex; Sing'oei, Valentine; Rombosia, Kevin; Ochieng, Christopher; Desai, Priyanka; Wolfman, Vanessa; Coakley, Peter; Lee, Elizabeth H; et al.
Abstract: Background: Children and adolescents living with HIV (CALHIV) face unique challenges, including poorer treatment outcomes, risk for drug-resistance mutations (HIVDRMs), and limited drug formulations. We estimated viral suppression (VS) prevalence and evaluated predictors of VS and HIVDRMs in Kenya. Methods: From 2018–2020, CALHIV 1–19 years on antiretroviral therapy (ART) >6 months were enrolled in this cross-sectional study. Participants underwent viral load (VL) testing; those with VL ≥1000 copies/mL had HIVDRM testing. Sociodemographic questionnaires and medical record abstraction were completed. VS prevalence (VL <1000 copies/mL) was estimated; robust Poisson regression models were used to estimate prevalence ratios (PRs) and 95% CIs for associations between potential predictors of VS. Results: Nine hundred and sixty-nine participants were enrolled. VS prevalence was .80 (95% CI: .78–.83). Being on ART >24 months (adjusted PR [aPR]: 1.22; 95% CI: 1.06–1.41), an integrase strand transfer inhibitor–containing regimen (1.13; 1.02–1.26), and attending a level 3 health facility (1.23; 1.11–1.36) were associated with VS. Missing ≥3 doses of ART in the past month (aPR: .73; 95% CI: .58–.92), having a viremic mother with HIV (.72; .53–.98), and having 3–7 (.90; .83–.97), 8–13 (.89; .82–.97), or ≥14 (.84; .77–.92) compared with <2 adherence counseling referrals were inversely associated with VS. A high proportion (n = 119, 81.5%) of unsuppressed participants had evidence of any major HIVDRM. Conclusions: HIV treatment programs should target interventions for pediatric patients at risk for treatment failure—namely, those with a caregiver with failed VS and those struggling with adherence. Abstract : Viral suppression prevalence was 80% among children/adolescents living with HIV. Missing ART doses, unsuppressed maternal viral load, and adherence counseling referrals were inversely associated with viral suppression, while on ART ≥2 years and an INSTI-containing regimen was associated with suppression.